(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Male cat (tomcat) neutering is a common surgical procedure performed to control overpopulation and reduce undesirable behaviors such as aggression, roaming, vocalization, and urine spraying. This case study documents the surgical sterilization of a 2.3-kg tomcat presented to the PMAC Veterinary Teaching Hospital, Sylhet, Bangladesh. Although both surgical and non-surgical sterilization techniques are available, permanent surgical removal of the testicles remains the most widely practiced and reliable method. In this case, bilateral orchiectomy was performed under general anesthesia following proper aseptic preparation and shaving of the operative site. General anesthesia was achieved using a combination of xylazine hydrochloride (1.1 mg/kg), atropine sulfate (0.04 mg/kg), and ketamine hydrochloride (15 mg/kg). Both testicles were removed, and the spermatic cords were ligated using absorbable sutures. Post-operative management included a five-day course of antibiotics and anti-inflammatory drugs. No post-surgical complications were observed, and the surgical wound healed uneventfully without the use of skin sutures. This case demonstrates that routine surgical neutering of tomcats, when performed using proper aseptic techniques and appropriate anesthetic protocols, is a safe, feasible, and effective procedure. Furthermore, it highlights the importance of surgical sterilization in population control and behavioral management while emphasizing the advantages of surgical neutering as a permanent sterilization method. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 501-506